FAKTOR–FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP WILAYAH JAKARTA UTARA - RIAN SUMARTA; MELIAWATI MELIAWATI (Media Bisnis, 2019)
The Objective of the research is to determine effect of taxpayer awareness, tax sanction, knowledge and understanding of taxation, tax socialization, service quality of tax authorities and implementation of e-filing system against individual taxpayer compliance in KPP North Jakarta area. Object used in this research isindividual taxpayer have Taxpayer Registration Number and registered in KPP North Jakarta area. The samples in this research consists 118 taxpayer respondents. The method of sample in this research used conveniencesampling method. The result showed that variable taxpayer awareness, knowledege, and understanding of taxation has influenced against individual taxpayer compliance. While other variables as tax sanction, service quality of tax authorities, implementation of e-filing system, tax socialization has not influenced against individual taxpayer compliance.